(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
A reversed-phase high performance liquid chromatography (RP-HPLC) method with ultraviolet detection was developed and validated for the simultaneous quantification of antiretroviral drugs lamivudine (3TC), stavudine (d4T), and zidovudine (AZT) in perfusate samples obtained from the Single-Pass Intestinal Perfusion studies. The chromatographic analysis was performed using a Gemini C18 column and didanosine as internal standard (IS). The following parameters were considered for the validation procedure: system suitability, accuracy, precision, linearity and selectivity. The limits of detection were 0.32 µg/mL for 3TC, 0.11 µg/mL for d4T and 0.45 µg/mL for AZT and the limits of quantification were 1.06 µg/mL for 3TC, 0.38 µg/mL for d4T and 1.51 µg/mL for AZT. Repeatability and intermediate precision ranged from 1.05 to 1.31 and 1.50 to 1.87, respectively, and are expressed as percent of relative standard deviation (RSD). Based on these results, the developed and validated RP-HPLC method can be used for simultaneous determination of 3TC, d4T, and AZT in perfusate samples. Furthermore, this method is simple and adequate for measurements of the antiretroviral drugs in the same sample, since those compounds are mostly co-administered. Besides, this work can be used as an initial base for the development of similar methods in the same conditions presented in our study.